Decline in photosynthetic nitrogen use efficiency with leaf age and nitrogen resorption as determinants of leaf life span - Escudero, A.; Mediavilla, S. (Journal of Ecology, 2003)
* 1Cost-benefit models predict that leaf life span depends on its initial photosynthetic rate and construction cost and on the rate of decline in photosynthesis with age. Leaf gas exchange rates and N contents were measured in nine woody evergreen Mediterranean species with different leaf life spans to determine the effects of leaf ageing on photosynthetic N use efficiency (PNUE). N costs of leaf construction were assumed to be in part dependent on N resorption from senescing leaves. * 2Leaf ageing had significant negative effects on photosynthetic rates per unit leaf area. As N content per unit leaf area did not decline until the end of leaf life, PNUE also decreased with age. PNUE generally declined faster in species with a shorter leaf life span. There were no significant interspecific differences in maximum CO2 assimilation rates per unit leaf area and in N resorption that could be related to differences in leaf life span. * 3As PNUE decreases with leaf age, shedding of the older leaves and retranslocation of N to the current year's leaf biomass would result in an increase in the mean instantaneous efficiency of use of the N retranslocated. However, total CO2 assimilation can be improved by such shedding only when the increase in the efficiency of use of the remobilized N compensates for the remaining N lost in the shed leaves. * 4The photosynthesis of the old leaf cohorts exceeded the increase in photosynthesis that would be obtained from the N retranslocated to the younger leaves, given the observed efficiencies of N resorption. The retention of old leaves thus resulted in a higher whole-canopy CO2 assimilation, despite their low PNUE.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: leaf life span; N resorption; photosynthetic nitrogen use efficiency; Pinus spp.; Quercus spp

Decline in photosynthetic nitrogen use efficiency with leaf age and nitrogen resorption as determinants of leaf life span - Escudero, a; Mediavilla, S (Journal of Ecology, 2003)
* 1Cost-benefit models predict that leaf life span depends on its initial photosynthetic rate and construction cost and on the rate of decline in photosynthesis with age. Leaf gas exchange rates and N contents were measured in nine woody evergreen Mediterranean species with different leaf life spans to determine the effects of leaf ageing on photosynthetic N use efficiency (PNUE). N costs of leaf construction were assumed to be in part dependent on N resorption from senescing leaves. * 2Leaf ageing had significant negative effects on photosynthetic rates per unit leaf area. As N content per unit leaf area did not decline until the end of leaf life, PNUE also decreased with age. PNUE generally declined faster in species with a shorter leaf life span. There were no significant interspecific differences in maximum CO2 assimilation rates per unit leaf area and in N resorption that could be related to differences in leaf life span. * 3As PNUE decreases with leaf age, shedding of the older leaves and retranslocation of N to the current year's leaf biomass would result in an increase in the mean instantaneous efficiency of use of the N retranslocated. However, total CO2 assimilation can be improved by such shedding only when the increase in the efficiency of use of the remobilized N compensates for the remaining N lost in the shed leaves. * 4The photosynthesis of the old leaf cohorts exceeded the increase in photosynthesis that would be obtained from the N retranslocated to the younger leaves, given the observed efficiencies of N resorption. The retention of old leaves thus resulted in a higher whole-canopy CO2 assimilation, despite their low PNUE.
Keywords: leaf life span; N resorption; photosynthetic nitrogen use efficiency; Pinus spp.; Quercus spp